Reading and writing behaviors of some four and five year old children during sociodramatic play (2006)
This study identified and described reading and writing behaviors of four and five year old children during sociodramatic play. Data were gathered from two preschool classrooms using naturalistic observation method. Twenty-four children were observed for 10 days during the entire duration of Free Play period as they engaged in sociodramatic play at the Dramatic Play Area. Results indicated that children's reading and writing behaviors are closely tied to the experiences with their environment. Furthermore, sociodramatic play episodes could give way to numerous opportunities for children to practice their emerging knowledge of print and its uses. The teacher's ability to work within these contexts elaborated further and increased the quantity and variety of children's literacy attempts. Therefore, Dramatic Play Areas should respond to children's needs and interests and contain appropriate and accessible literacy tools. Researches should head towards documenting further sociodramatic play and its role in literacy among preschoolers.
Keywords: Early childhood education; Drama in education; Social interaction in children